1988
DOI: 10.1016/s0022-5347(17)42913-2
|View full text |Cite
|
Sign up to set email alerts
|

Rat Colonic Carcinogenesis After Ureterosigmoidostomy: Pathogenesis and Immunohistological Study

Abstract: A group of 44 rats underwent the equivalent of a ureterosigmoidostomy (US), while a second group of 18 rats underwent a pediculated graft (PG) of urothelial tissue in the sigmoid wall. Histological lesions were observed in the colon near the bladder colon junction in US rats exclusively. These lesions included dysplasias (5/23), cystic glands (4/23) and 10 neoplasms (9/23), three of which were adenomas, showing elements of juvenile polyp and tubular adenoma in one case. The seven other tumors showed typical hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 22 publications
0
5
1
1
Order By: Relevance
“…The presence of dysplasia is expected after vesico-colonic anastomosis in rats (2,16). In our investigation the presence of dysplasia was not significantly different from the controls, which could possibly be attributed to the timing of the experiment.…”
Section: Commentscontrasting
confidence: 46%
“…The presence of dysplasia is expected after vesico-colonic anastomosis in rats (2,16). In our investigation the presence of dysplasia was not significantly different from the controls, which could possibly be attributed to the timing of the experiment.…”
Section: Commentscontrasting
confidence: 46%
“…Vasectomised rats served as a control group. Other authors continued with this model and reported up to 80% of tumours (Gittes, 1986;Daher et al, 1988). Harguindey et al (1976) suggested that irritation produced by the excessive concentration of electrolytes was responsible for carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Another theory of carcinogenesis has been suggested involving bacterial activation of endogenously formed N-nitrosamine. [16][17][18][19][20] In this case, it is unclear whether the tumour originated from the skin or the ileum. Given our patient's chronic catheterization, chronic inflammation of the stoma and Monti ileal segment may likely be the predisposing factor for developing squamous metaplasia and SCC in situ.…”
Section: Discussionmentioning
confidence: 99%